Watching Together: Local Media and Rural Civic Engagement. (31st March 2021) - Thompson, Jack
Abstract: Civic engagement involves active participation in political and nonpolitical contexts in one's community. Research consistently demonstrates that sociodemographic factors, neighborhood context, community size, and media use are all important antecedents of robust civic engagement. This paper focuses on the intersection between these latter two factors. My paper draws on multiple streams of research in the rural sociology and communication literature to develop a theoretical framework where rural individuals' use of local media promotes greater civic engagement. Using data from the 2018 Local News Survey, results show that the use of local newspapers and online news websites for local news and information leads to a higher probability of participation in local activities and local groups in one's community. However, results also show that getting local news and information from traditional formats such as local TV stations may no longer be associated with an increased probability of being an active citizen in rural communities.